How Does Job Coaching Help Disability Insurance Recipients Work While on Claim? - Sébastien Fontenay; Ilan Tojerow (Institute of Labor Economics (IZA), 2022)
We evaluate the effects of a Supported Employment (SE) program aimed at Disability Insurance (DI) recipients with mental conditions. The program is characterized by a "work-first" approach, which includes intensive job coaching and follow-along support. Using a Randomized Control Trial with more than 660 participants over a follow-up period of 18 months, we compare the benefits of this newly introduced program to regular vocational rehabilitation services traditionally used in Belgium. We find that SE increases the probability that DI recipients with mental conditions work while on claim and reduces their reliance on DI benefits. Specifically, we estimate that 18 months after the start of their return-to-work program, participants in the SE group are 9.5 percentage points more likely to be working, and receive 6% less in DI benefits than those in the control group.
Keywords: H55; I38; J24; 330; employment support; disability insurance; mental health; randomized experiment